1998
DOI: 10.1159/000069461
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Monkey Model Sensitized with Mite Antigen

Abstract: Background: Monkeys are considered to have an immune system very similar to that of humans, as compared with mice, rats, and guinea pigs. Although primate allergic models to several pollen allergens have been developed, no model of house dust mite allergy has been reported. In this study, we attempted to induce type I allergy to mite allergens in rhesus monkeys. Methods: Six rhesus monkeys were immunized subcutaneously with crude mite extract adsorbed on aluminum hydroxide for 4 months. Then 5 monkeys positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…We first succeeded to induce asthmatic responses by the sensitization with DNP-As. Then, we tried to induce asthmatic responses by the sensitization with mites, because dust mites are commonly associated with human asthma (19) and has been shown to be effective in inducing symptoms of asthma in common laboratory animals, including mice (20,21), rats (22), rhesus monkeys (9,15), and rabbits (23). In addition, natural sensitivity to dust mites had been documented in monkeys (24), increasing the relevance of the allergen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We first succeeded to induce asthmatic responses by the sensitization with DNP-As. Then, we tried to induce asthmatic responses by the sensitization with mites, because dust mites are commonly associated with human asthma (19) and has been shown to be effective in inducing symptoms of asthma in common laboratory animals, including mice (20,21), rats (22), rhesus monkeys (9,15), and rabbits (23). In addition, natural sensitivity to dust mites had been documented in monkeys (24), increasing the relevance of the allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, although wildcaught cynomolgus monkeys (10 -13) and squirrel monkeys (14) sensitive to inhaled Ascaris suum allergen had been used, these wild-caught monkeys are not currently available. Recently, several studies showed that sensitization of monkeys with allergens could elicit allergen-specific IgE production (9) and allergic asthma symptoms upon allergen provocation (15,16). However, a long period of time is required for the development of these models (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of primate studies have used clinically meaningful aeroallergens, such as ragweed [11] or house dust mite (HDM) delivered in aerosol form [6,12,13]. PLOPPER and HYDE [3] addressed the validity of these models at the anatomical and cellular levels, and ZOU et al [14] documented changes in gene expression by microarray profiling following acute challenge with allergen.…”
mentioning
confidence: 99%
“…Large animal models of asthma have been developed in sheep [63], dogs [64] and nonhuman primates (macaques) [65][66][67][68][69]. The rhesus monkey model of asthma is used because of the genetic and physiological similarity to humans that allows pulmonary function measurements commonly used in humans [66].…”
Section: Uniqueness Of the Rhesus Monkey Model Of Asthmamentioning
confidence: 99%